Adoption of Digital Marketing in E- Recruitment Success: A Quantitative Study on Bangladesh Perspective - Dr. Rumana Afroze; Sujana Shafi (Journal of Management Research, 2024)
This study’s purpose and strategies are to unwrap factors for the adoption of digital marketing strategies in the success of e-recruitment in Bangladesh. It also focuses on organizational perception, brand value, candidate and employer e- recruitment decisions in Bangladesh. In order to achieve the research objectives, a quantitative research has been done. A total of 138 human resource professionals from eleven prestigious job sectors in Bangladesh were contacted to participate in this study’s survey. To conduct the research, a structured questionnaire was used. The collected data was analyzed using statistical analysis. Statistical tests like, descriptive analysis, reliability correlations, factor analysis and regression test were used to pursue the objective of analysis. The result has proved that adoption of digital marketing has significant impact on e- recruitment effectiveness. This study has practical implications for especially human resource departments and marketing managers and, such as the implementation of an integrated digital marketing and communication strategy with successful HR e-recruitment. This research incorporates digital marketing insights into well-established HRM fields.